7z-9=3

Simple and best practice solution for 7z-9=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7z-9=3 equation:


Simplifying
7z + -9 = 3

Reorder the terms:
-9 + 7z = 3

Solving
-9 + 7z = 3

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 7z = 3 + 9

Combine like terms: -9 + 9 = 0
0 + 7z = 3 + 9
7z = 3 + 9

Combine like terms: 3 + 9 = 12
7z = 12

Divide each side by '7'.
z = 1.714285714

Simplifying
z = 1.714285714

See similar equations:

| 4/3=10/x | | -4p=44 | | 11-a=13 | | 2x+14=-28 | | 6(-6x+4)=-8(4x-6) | | -x-13+25=-3+52 | | 75x-2=-14 | | (12x+1)=(20x+19) | | 5(r-8)-4(6r-4)=-8r-8r | | 2x=5x+21-6 | | 3(1+11)= | | 5a^2+60a+180=0 | | 3x^2-18x-19=0 | | 2(1+x)=3(x+4) | | 9x+70=360 | | 2x(x-4)(x+8)=0 | | 3(5p-3)=5(p-1) | | 14x-3(2x-5)+2(5x-3)=6-5(2x-9) | | 3(y+30)=6y-4 | | 5(v-5)+3(v+2)=-4v+7+3v-2 | | 3(x+5)=5x+2.5 | | 117=6x-12+3x+3 | | (34-2)y=8 | | 8(5x-3)+4(1-8x)=3x-8+3x-2 | | 4u^2-2u=0 | | 10x5/2 | | 2p-10)/(8p-40) | | 6(9d)=3d | | 180=x+(0.05+x) | | (9x-2y)-(6x+2y)= | | 6(x-4)-4=8 | | 4logx-3logx=12 |

Equations solver categories